2002
DOI: 10.1002/jbm.10295
|View full text |Cite
|
Sign up to set email alerts
|

Liquid acrylate‐endcapped biodegradable poly(ϵ‐caprolactone‐co‐trimethylene carbonate). II. Computer‐aided stereolithographic microarchitectural surface photoconstructs

Abstract: Advanced micromedical devices may require computer-aided photofabrication, by which microarchitectural surface design and entire macroshaped body design are feasible. Liquid acrylate-endcapped poly(epsilon-caprolactone-co-trimethylene carbonate)s, poly(CL/TMC)s, prepared using trimethylene glycol (TMG) or poly(ethylene glycol) (PEG) as an initiator and an acrylate group for subsequent terminal capping, were used as photocurable copolymers. The stereolithographically microarchitectured photoconstructs were prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 10 publications
1
78
0
1
Order By: Relevance
“…Chloroform was used for selective solvation of the polymeric particles, resulting in particle adhesion upon chloroform evaporation. Matsuda [46] developed ultraviolet (UV) radiationÀpolymerizable and biodegradable materials for SLA, [38] and Hutmacher [47] used the FDM technique [40] and optimized its building process parameters in order to permit the use of polycaprolactone for building scaffolds with a honeycomb internal architecture. Below is a short description of some of the major AM techniques used today for fabrication of 3D polymeric objects.…”
Section: Bioprinting Methodologiesmentioning
confidence: 99%
“…Chloroform was used for selective solvation of the polymeric particles, resulting in particle adhesion upon chloroform evaporation. Matsuda [46] developed ultraviolet (UV) radiationÀpolymerizable and biodegradable materials for SLA, [38] and Hutmacher [47] used the FDM technique [40] and optimized its building process parameters in order to permit the use of polycaprolactone for building scaffolds with a honeycomb internal architecture. Below is a short description of some of the major AM techniques used today for fabrication of 3D polymeric objects.…”
Section: Bioprinting Methodologiesmentioning
confidence: 99%
“…Results showed that higher coumarin functionality and UV light intensity, and a reduced layer thickness of the liquid film precursor increases the photocuring reaction. The same oligomers were used by Matsuda and Mizutani [66] to produce photocurable copolymers, using trimethylene glycol or PEG as initiator and an acrylate group (acryloyl chloride) to end-functionalize the oligomers. Different structures were produced using the photocurable copolymers through stereolithography, as shown in Fig.…”
Section: Synthetic Polymers and Hydrogelsmentioning
confidence: 99%
“…Resins based on poly(propylene fumarate), poly(ethylene glycol), poly(D,L-lactide) and (co)polymers of trimethylene carbonate and -caprolactone have been investigated for these purposes. [62,[65][66][67][68][69][70][71][72] The use of these resins results in the formation of brittle or rigid networks.…”
Section: Stereolithographymentioning
confidence: 99%